Social media, youth and everyday life in Kenya. (1st June 2017) - Ndlela, Martin N.; Mulwo, Abraham
With an increasing accessibility of smartphones and mobile Internet, social media are becoming an integral part of everyday life for young people in Kenya. The use of new social media tools like Facebook, Twitter and WhatsApp is quickly changing in the country. Previous research on new media, however, indicates socio-demographic differences in the access, appropriation and use of new technologies. This article aims at advancing our understanding of how young people in developing countries are appropriating and using new social media platforms. It examines the multiple ways in which young people in Kenya use social media platforms and how they use these new spaces to connect, interact, communicate and engage on different issues. The article argues that the new social media configurations are invariably making possible access to alternative spaces, relatively 'free' from mainstream communication platforms. These changes have implications on different aspects of social change processes such as sociocultural and socio-economic changes in the Kenya.